Effectiveness of Implementing the TukuoYuk Platform in the Development of the MSME Sector in Sidoarjo Regency - Hidayahtullah, Ananda Putri; Mursyidah, Lailul (Universitas 17 Agustus 1945 Surabaya, 2024)
The COVID-19 pandemic caused Indonesia to experience a crisis that had a broad impact and forced all levels of society to switch to the digital world. This encourages MSMEs as business actors to rise from the economic downturn by taking advantage of current technological developments. The Sidoarjo Regency Government is taking steps to develop MSMEs through an application that utilizes information technology called TukuoYuk. The TukuoYuk application is an online platform encouraging MSME players to perform promotions more intensively. This research aims to describe and analyze the application of the TukuoYuk platform in developing MSMEs in Sidoarjo Regency. This research uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. The data analysis technique in this research uses an interactive analysis model by Miles and Huberman, consisting of four components: data collection, data reduction, data presentation, and concluding. This research shows that the implementation of the TukuoYuk platform in Sidoarjo Regency is seen from five indicators. First, understanding the platform program still needs to be improved. Second, the platform's targeting accuracy could be more optimal because of clear procedures. Third, the platform's punctuality has yet to be yet to be achieved due to the absence of clear SOPs. Fourth, due to a lack of design, the platform's objectives have yet to be achieved optimally. Fifth, fundamental changes to the platform are still limited.